Jatuh Tegangan Pada Feeder Tegangan Menengah Gardu Induk Garuda Sakti Berdasarkan Model Distribusi Beban - Arga Siahaan; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The additional load that occurs in medium voltage feeders due to load growth that occurs over time results in the electrical system being no longer by its original design or even experiencing a decrease in performance. Therefore, it is necessary to analyze the performance of the medium voltage feeder gradually. In analyzing the performance of a medium voltage feeder, the approach method is a method that can be used to calculate the voltage drop. the calculation of the voltage drop using the approach method is carried out by modeling the distribution of the load contained in the feeder, then calculating the voltage drop based on the load distribution model contained in the feeder. Based on the results of the calculation of the voltage drop using the approach method carried out on the gurami, salmon, and lele feeder at Garuda Sakti Substation, the voltage drop values obtained are 432.2 V on the gurami feeder, 1,160.2 V on the salmon feeder, and 1,134.7 V on the lele feeder. The calculation results are then compared with the simulation results of Etap 16.0, which has a voltage drop of 422 V on the gurami feeder, 1,206 V on the salmon feeder and 1,096 V on the lele feeder. The comparison results show that the error between the calculation of the voltage drop using the approximation method and the simulation results of Etap 16.0 is 2.41% on the gurami feeder, 3.76% on the salmon 3.53% on the lele feeder.Keyword: medium voltage feeder, load distribution model, voltage drop